The Influence of Nursing Skills Learning Media Through Video on the Achievement of Student Competencies in the Installation of Infusions - PAY, Jenny Ramadona; Sundari, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze how the influence of video learning media on student competency achievement. The method used in this study was carried out by taking data from PubMed, ProQuest, Google Scholar databases, which were found in 2015-2021. The results showed that some of the learning media used by students were video. In conclusion, video as a learning medium is very influential in increasing knowledge, helping to get information about assignments, knowing the development of information, and can be used as material to deepen the material. Keywords: Students, Learning Media, Video